SEISMIC OBSERVATION WITH LOCAL TELEMETRY NETWORK AROUND SYOWA STATION, EAST ANTARCTICA (2) - アカマツ, ジュンペイ; イチカワ, ノブオ; カミヌマ, カツタダ; AKAMATSU, Junpei; ICHIKAWA, Nobuo; KAMINUMA, Katsutada (National Institute of Polar Research, 1990)
P(論文) A local telemetry seismic network was established around Syowa Station to study local seismicity and wave characteristics in the Lutzow-Holm Bay region, East Antarctica. More than 14000 events were recorded during the period from June 1987 through January 1989. Most of them were icequakes, though 1043 teleseisms and 9 local earthquakes were identified. Local earthquakes of magnitude ranging from -1 to 3 occurred in the coastal and offshore regions of the continent. In the observational period, no earthquakes with M larger than 2 seemed to occur within 500km under the continent. The locations of local earthquakes were discussed in relation to possible faults inferred from surface geology and submarine topography. Apparent phase velocities were examined to discuss the velocity structures and source depths.Locations of iceshocks of sea ice were examined to confirm the velocity model. It was clarified that iceshocks occurred mainly in the boundary area between the multi-year ice and the first-year ice. departmental bulletin paper